Nutrition Labelling’s Impact on Consumption Patterns and Nutrition Awareness in Community: A Literature Review - Wahyuni, Tri; Flora, Rostika; Rahmiwati, Anita (Journal of Food and Pharmaceutical Sciences, 2025)
Background: Nutrition labelling on food packaging has become an essential tool for assisting consumers in making healthier food choices. Various label styles are used in different nations, but their usefulness varies according to the design and ease of understanding by customers, the aim of this study is to determine the impact of nutrition labels on consumption pattern and nutrition awareness; Methods: This study used a descriptive literature review with 2 data sources, namely PubMed and Google Scholar. The keywords used are "Nutrition Labelling" OR "Food Labels" AND "Healthy Food Choices" AND “Nutrition Awareness” with predetermined inclusion and exclusion criteria, then article analysis was carried out to achieve the objectives; Results: A total of 5 articles met the criteria and objectives of the study, the study's findings indicate show that front-of-pack nutrition labeling (FoPL) is essential for directing better food choices and increasing consumer nutrition awareness; and Conclusions: Nutrition labelling has been found to play a significant effect in raising nutritional knowledge and affecting people's consumption habits. Labels like Multiple Traffic Lights (MTL), Traffic Light Food Labels (TLF), and Nutri-Score regularly encourage healthy food choices by offering information that is simple to understand and visually appealing.